Respuesta :
Answer:
A. [tex](y-3)=-3(x-1)[/tex]
Step-by-step explanation:
We have been given coordinates of two points (0, 6) and (1, 3). We are asked o find the equation of line passing through the given points in point- slope form.
We know that the point-slope form of equation is in format: [tex](y-y_1)=m(x-x_1)[/tex], where,
[tex]m=\text{Slope of line}[/tex],
[tex](x_1,y_1)=\text{Coordinates of a point on line}[/tex]
First of all, we will find the slope of line using coordinates of given point in slope formula as shown below:
[tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex]
[tex]m=\frac{3-6}{1-0}[/tex]
[tex]m=\frac{-3}{1}[/tex]
[tex]m=-3[/tex]
Upon substituting [tex]m=-3[/tex] and coordinates of point (1, 3) in point-slope form of equation we will get,
[tex](y-3)=-3(x-1)[/tex]
Therefore, option A is the correct choice.